Camera‐augmented mobile C‐arm (CamC): A feasibility study of augmented reality imaging in the operating room. Issue 2 (21st December 2017) - von der Heide, Anna Maria; Fallavollita, Pascal; Wang, Lejing; Sandner, Philipp; Navab, Nassir; Weidert, Simon; Euler, Ekkehard
Abstract: Background: In orthopaedic trauma surgery, image‐guided procedures are mostly based on fluoroscopy. The reduction of radiation exposure is an important goal. The purpose of this work was to investigate the impact of a camera‐augmented mobile C‐arm (CamC) on radiation exposure and the surgical workflow during a first clinical trial. Methods: Applying a workflow‐oriented approach, 10 general workflow steps were defined to compare the CamC to traditional C‐arms. The surgeries included were arbitrarily identified and assigned to the study. The evaluation criteria were radiation exposure and operation time for each workflow step and the entire surgery. The evaluation protocol was designed and conducted in a single‐centre study. Results: The radiation exposure was remarkably reduced by 18 X‐ray shots 46% using the CamC while keeping similar surgery times. Conclusions: The intuitiveness of the system, its easy integration into the surgical workflow, and its great potential to reduce radiation have been demonstrated.